Publishing Hierarchies in Sociology - Wang, Rachel E. (Tufts Archival Research Center, 2022)
Various academic disciplines possess internal hierarchies that are reflected in the unequal prestige of journals. These journal hierarchies reproduce conceptions of what is mainstream scholarship. For sociology specifically, the American Journal of Sociology (AJS) and the American Sociological Review (ASR) persistently reside at the top of the publishing hierarchy. It is of interest to explore how these publishing hierarchies reproduce and maintain epistemic exclusions. In this project, I conducted both qualitative interviews with sociologists and a systematic content analysis of the demographics of authors published in AJS/ASR. The interviews elucidated the meaning of AJS/ASR for scholars who have and have not published in these top, generalist journals. While some scholars viewed AJS/ASR as ‘cutting edge,’ other scholars described AJS/ASR as a ‘conservative’ entity that excludes methods and topics that stray from a narrow understanding of what constitutes ‘mainstream’ sociology. Comparing the demographics of AJS/ASR authors with the demographics of sociologists in the field at large in select years revealed that Black and Hispanic/Latinx scholars were underrepresented, while White and Asian American/Pacific Islander scholars were overrepresented. Ultimately, this study proffers insight into the ways in which the field’s publishing hierarchies refract and maintain disparities in who gets to produce knowledge that is centered and valorized.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Sociology.; Advisor: Caleb Scoville and Daanika Gordon.